Effect of glycosylation on protein folding: From biological roles to chemical protein synthesis - Chunchun Hao; Qijie Zou; Xuerong Bai; Weiwei Shi (iScience)
Summary: Chemical protein synthesis has become an important tool in biotechnology and synthetic biology for producing proteins with complex structures. However, achieving correct folding in vitro remains a significant challenge. Glycosylation, a ubiquitous modification, stabilizes folding intermediates, prevents aggregation, and accelerates folding in both cellular and cell-free systems. In this review, we discuss the dual role of glycosylation in biological systems and in vitro experiments, focusing on how it promotes protein folding and stability. We also discuss the temporary glycosylation scaffold strategy for chemical protein synthesis, which offers a reversible approach to guide protein folding without leaving permanent modifications. This strategy provides a promising solution to the challenges of in vitro folding and holds significant potential to produce therapeutic proteins and the development of synthetic proteins with precise structural requirements.